Anticorrosive material containing polymethyl terephthalate and preparation method thereof

By combining polymethyl terephthalate, carbon fiber, phenolic resin, quaternary ammonium modified graphene oxide, amino acid benzooxazine, bentonite and other components, anticorrosion materials with good flame retardant properties are prepared, which solves the problem of insufficient flame retardant effects of existing anticorrosion materials and achieves higher anticorrosion and flame retardant effects.

CN119505487APending Publication Date: 2025-02-25SHANDONG ZHONGKE YUYE NEW ENERGY MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411630903.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The flame retardant effect of existing anticorrosion materials is insufficient and cannot effectively protect the materials from damage caused by high temperatures and fires.

Method used

Using anticorrosion materials containing polymethyl terephthalate, anticorrosion materials with good flame retardant properties are prepared by combining polymethyl terephthalate, carbon fiber, phenolic resin, quaternary ammonium salt modified graphene oxide, amino acid benzooxazine, bentonite and other components.

Benefits of technology

It significantly improves the flame retardant performance and corrosion resistance of anticorrosion materials, and can effectively protect the materials under high temperature and fire conditions and extend their service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, and discloses a polymethyl terephthalate-containing anticorrosive material and a preparation method thereof.The preparation method comprises the steps that polymethyl terephthalate, carbon fibers, phenolic resin, quaternary ammonium salt modified graphene oxide, amino acid benzoxazine and bentonite are added into a stirrer and stirred, and a mixture is obtained; the corrosion-resistant material containing the polymethyl terephthalate is prepared. Phosphorus, nitrogen and silicon elements contained in the quaternary ammonium salt modified graphene oxide and amino acid benzoxazine have good flame retardant effects, and benzoxazine can form a heat-resistant phenolic resin structure at high temperature, so that the material shows higher thermal decomposition temperature and flame retardant property. The quaternary ammonium salt group and the graphene oxide structure improve the corrosion resistance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to an anticorrosive material containing polymethyl terephthalate and a preparation method thereof. Background Art

[0002] Anticorrosion materials are a type of material used to protect materials from chemical and electrochemical corrosion. They are widely used in many fields, including but not limited to petrochemicals, marine engineering, urban infrastructure, rail transit, and aerospace. Anticorrosion materials not only ensure the quality and safety of engineering projects, but also extend their service life. For example, patent CN103184001B discloses an anticorrosion material and its preparation method. The anticorrosion material prepared by the invention has the advantages of good leveling, good surface toughness, strong adhesion, and environmental protection, but its flame retardant effect has not been improved. Summary of the invention

[0003] 1. Technical issues to be resolved In view of the deficiencies of the prior art, the present invention provides an anti-corrosion material containing polymethyl terephthalate and a preparation method thereof, which has good flame retardant and anti-corrosion effects.

[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical scheme: an anti-corrosion material containing polymethyl terephthalate, comprising the following components by weight: 10-15 parts by weight of polymethyl terephthalate, 4-8 parts by weight of carbon fiber, 8-20 parts by weight of phenolic resin, 4-9 parts by weight of quaternary ammonium salt-modified graphene oxide, 3-7 parts by weight of amino acid-based benzoxazine, and 1-2 parts by weight of bentonite.

[0005] Preferably, the preparation method of the quaternary ammonium salt modified graphene oxide is: (1) Under a nitrogen atmosphere, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to tetrahydrofuran solvent, stir and dissolve, continue to add azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane, react at 65-85°C for 10-14h, and after the reaction is completed, distill under reduced pressure and vacuum dry for 6-8h to obtain phosphorus-containing tertiary aminosilane; (2) Add 2,2-bis(bromomethyl)-1,3-propylene glycol and phosphorus-containing tertiary aminosilane to acetone solvent, stir evenly, then continue to add 3-5 mol / L sodium hydroxide aqueous solution, react at 75-90°C for 4-6 hours. After the reaction is completed, neutralize, concentrate, filter, wash and dry to obtain intermediate 1 (3) Ultrasonic dispersion of 5-8 parts by weight of graphene oxide in 45-70 parts by weight of thionyl chloride, after uniform dispersion, reacting at 50-75° C. for 3-6 hours to obtain acylated graphene oxide; adding acylated graphene oxide and intermediate 1 into N,N-dimethylformamide solvent, stirring and mixing, continuously adding triethylamine catalyst thereto, reacting at 70-90° C. for 4-7 hours, and then distilling under reduced pressure, washing and drying to obtain quaternary ammonium salt-modified graphene oxide.

[0006] Preferably, in the (1), the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile initiator and bis(dimethylamino)methylvinylsilane is 1:0.01-0.03:1.1-1.4.

[0007] Preferably, the mass ratio of 2,2-bis(bromomethyl)-1,3-propylene glycol to phosphorus-containing tertiary aminosilane in (2) is 0.9-1.2:1.

[0008] Preferably, in said (3), the mass ratio of acylated graphene oxide, intermediate 1, and triethylamine catalyst is 1.3-1.5:1:0.02-0.04.

[0009] Preferably, the preparation method of the amino acid-based benzoxazine is: S1. Add glutamic acid to N,N-dimethylformamide solvent, stir to dissolve, continue to add intermediate 1 and p-toluenesulfonic acid catalyst, react at 90-110°C for 6-10h, and then distill under reduced pressure and wash to obtain intermediate 2; S2. Add 4-6 parts by weight of intermediate 2, 10-15 parts by weight of an aqueous solution of formaldehyde and 18-24 parts by weight of phenol into toluene solvent, fully dissolve them, and carry out cyclization reaction at 70-95°C for 10-16 hours. After completion, distill under reduced pressure, wash with deionized water, and recrystallize the crude product from dichloromethane to obtain amino acid-based benzoxazine.

[0010] Preferably, the mass ratio of glutamic acid, intermediate 1, and p-toluenesulfonic acid catalyst in S1 is 1:1.1-1.4:0.02-0.04.

[0011] Preferably, the preparation method of the anti-corrosion material containing polymethyl terephthalate is: adding polymethyl terephthalate, carbon fiber, phenolic resin, quaternary ammonium salt-modified graphene oxide, amino acid-based benzoxazine, and bentonite into a stirrer, stirring at 550-700 rpm for 2-3 hours, to obtain the anti-corrosion material containing polymethyl terephthalate.

[0012] 3. Beneficial technical effects The invention prepares the anticorrosive material containing polymethyl terephthalate by adding polymethyl terephthalate, carbon fiber, phenolic resin, quaternary ammonium salt modified graphene oxide, amino acid benzoxazine and bentonite into a stirrer and stirring the mixture.

[0013] The phosphorus, nitrogen and silicon elements contained in quaternary ammonium salt-modified graphene oxide and amino acid-based benzoxazine have good flame retardant effects. The phosphorus element contained therein can produce phosphoric acid and metaphosphoric acid, which are strong dehydrating substances, when heated, and can promote the dehydration of the material into carbon, thereby achieving a flame retardant effect; the nitrogen element contained therein can produce non-flammable gas when heated, dilute the concentration of flammable gas, and achieve the purpose of flame retardancy; the silicon element contained therein can not only absorb more heat, but also absorb heat to produce a glass-like substance, which covers the surface of the material, isolates material transportation and energy transfer, and achieves the purpose of flame retardancy; benzoxazine will form a heat-resistant phenolic resin structure at high temperature, so that the material exhibits a higher thermal decomposition temperature and flame retardant properties. In the present invention, bromine in 2,2-bis(bromomethyl)-1,3-propylene glycol and tertiary amine group in phosphorus-containing tertiary amine silane undergo quaternization reaction to generate quaternary ammonium salt, and a large number of hydroxyl groups are introduced at the same time, thereby obtaining intermediate 1, which is further reacted with acylated graphene oxide to increase the substitution degree of acylated graphene oxide, wherein the quaternary ammonium salt group and graphene oxide structure improve the anti-corrosion performance of the material; and polymethyl terephthalate itself has certain anti-corrosion performance. DETAILED DESCRIPTION Example 1

[0014] (1) Under a nitrogen atmosphere, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added to tetrahydrofuran solvent, stirred and dissolved, and then azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane were added thereto, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane was 1:0.01:1.1, and the reaction was carried out at 65°C for 10 hours. After the reaction was completed, the reaction was carried out by vacuum distillation and vacuum drying for 6 hours to obtain phosphorus-containing tertiary aminosilane; (2) Add 2,2-bis(bromomethyl)-1,3-propylene glycol and phosphorus-containing tertiary amino silane to acetone solvent, wherein the mass ratio of 2,2-bis(bromomethyl)-1,3-propylene glycol to phosphorus-containing tertiary amino silane is 0.9:1, stir evenly, then continue to add 3 mol / L sodium hydroxide aqueous solution, react at 75°C for 4 hours, and after the reaction is completed, neutralize, concentrate, filter, wash and dry to obtain intermediate 1; (3) Ultrasonic dispersion of 5 parts by weight of graphene oxide in 45 parts by weight of thionyl chloride, after uniform dispersion, reacting at 50° C. for 3 h to obtain chlorinated graphene oxide; adding chlorinated graphene oxide and intermediate 1 into N,N-dimethylformamide solvent, stirring and mixing, and continuously adding triethylamine catalyst thereto, wherein the mass ratio of chlorinated graphene oxide, intermediate 1, and triethylamine catalyst is 1.3:1:0.02, reacting at 70° C. for 4 h, and then distilling under reduced pressure after completion, washing and drying to obtain quaternary ammonium salt-modified graphene oxide; (4) Add glutamic acid to N,N-dimethylformamide solvent, stir to dissolve, and continue to add intermediate 1 and p-toluenesulfonic acid catalyst, wherein the mass ratio of glutamic acid, intermediate 1, and p-toluenesulfonic acid catalyst is 1:1.1:0.02, react at 90°C for 6h, and then distill under reduced pressure and wash to obtain intermediate 2; (5) 4 parts by weight of the intermediate 2, 10 parts by weight of an aqueous solution of formaldehyde, and 18 parts by weight of phenol were added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 70° C. for 10 h. After the reaction, the mixture was distilled under reduced pressure, washed with deionized water, and the crude product was recrystallized from dichloromethane to obtain an amino acid-based benzoxazine; (6) 10 parts by weight of polymethyl terephthalate, 4 parts by weight of carbon fiber, 8 parts by weight of phenolic resin, 4 parts by weight of quaternary ammonium salt-modified graphene oxide, 3 parts by weight of amino acid-based benzoxazine, and 1 part by weight of bentonite were added into a stirrer and stirred at 550 rpm for 2 h to obtain an anti-corrosion material containing polymethyl terephthalate. Example 2

[0015] (1) Under a nitrogen atmosphere, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added to tetrahydrofuran solvent, stirred and dissolved, and then azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane were added thereto, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane was 1:0.03:1.4, and the reaction was carried out at 85°C for 14 hours. After the reaction was completed, the reaction was carried out by vacuum distillation and vacuum drying for 8 hours to obtain a phosphorus-containing tertiary aminosilane; (2) Add 2,2-bis(bromomethyl)-1,3-propylene glycol and phosphorus-containing tertiary amino silane to acetone solvent, wherein the mass ratio of 2,2-bis(bromomethyl)-1,3-propylene glycol to phosphorus-containing tertiary amino silane is 1.2:1, stir evenly, then continue to add 5 mol / L sodium hydroxide aqueous solution, react at 90°C for 6 hours, and after the reaction is completed, neutralize, concentrate, filter, wash and dry to obtain intermediate 1; (3) ultrasonically dispersing 8 parts by weight of graphene oxide into 70 parts by weight of thionyl chloride, and after being evenly dispersed, reacting at 75° C. for 6 hours to obtain chlorinated graphene oxide; adding chlorinated graphene oxide and intermediate 1 into N,N-dimethylformamide solvent, stirring and mixing, and continuously adding triethylamine catalyst thereto, wherein the mass ratio of chlorinated graphene oxide, intermediate 1, and triethylamine catalyst is 1.5:1:0.04, reacting at 90° C. for 7 hours, and then distilling under reduced pressure after completion, washing and drying to obtain quaternary ammonium salt-modified graphene oxide; (4) Add glutamic acid to N,N-dimethylformamide solvent, stir to dissolve, and continue to add intermediate 1 and p-toluenesulfonic acid catalyst, wherein the mass ratio of glutamic acid, intermediate 1, and p-toluenesulfonic acid catalyst is 1:1.4:0.04, react at 110°C for 10 hours, and then distill under reduced pressure and wash to obtain intermediate 2; (5) 6 parts by weight of the intermediate 2, 15 parts by weight of an aqueous solution of formaldehyde, and 24 parts by weight of phenol were added to a toluene solvent, fully dissolved, and subjected to a cyclization reaction at 95° C. for 16 h. After the reaction, the mixture was distilled under reduced pressure, washed with deionized water, and the crude product was recrystallized from dichloromethane to obtain an amino acid-based benzoxazine; (6) 15 parts by weight of polymethyl terephthalate, 8 parts by weight of carbon fiber, 20 parts by weight of phenolic resin, 9 parts by weight of quaternary ammonium salt-modified graphene oxide, 7 parts by weight of amino acid-based benzoxazine, and 2 parts by weight of bentonite were added into a stirrer and stirred at 700 rpm for 3 hours to obtain an anti-corrosion material containing polymethyl terephthalate. Example 3

[0016] (1) Under a nitrogen atmosphere, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide was added to tetrahydrofuran solvent, stirred and dissolved, and then azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane were added thereto, wherein the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane was 1:0.02:1.3, and the reaction was carried out at 70°C for 12 hours. After the reaction was completed, the reaction was carried out by reduced pressure distillation and vacuum drying for 7 hours to obtain phosphorus-containing tertiary aminosilane; (2) Add 2,2-bis(bromomethyl)-1,3-propylene glycol and phosphorus-containing tertiary amino silane to acetone solvent, wherein the mass ratio of 2,2-bis(bromomethyl)-1,3-propylene glycol to phosphorus-containing tertiary amino silane is 1.1:1, stir evenly, then continue to add 4 mol / L sodium hydroxide aqueous solution, react at 82°C for 5 hours, and after the reaction is completed, neutralize, concentrate, filter, wash and dry to obtain intermediate 1; (3) ultrasonically dispersing 6 parts by weight of graphene oxide into 60 parts by weight of thionyl chloride, and after being evenly dispersed, reacting at 70° C. for 5 hours to obtain chlorinated graphene oxide; adding chlorinated graphene oxide and intermediate 1 into N,N-dimethylformamide solvent, stirring and mixing, and continuously adding triethylamine catalyst thereto, wherein the mass ratio of chlorinated graphene oxide, intermediate 1, and triethylamine catalyst is 1.4:1:0.03, reacting at 80° C. for 5 hours, and then distilling under reduced pressure after completion, washing and drying to obtain quaternary ammonium salt-modified graphene oxide; (4) Add glutamic acid to N,N-dimethylformamide solvent, stir to dissolve, and continue to add intermediate 1 and p-toluenesulfonic acid catalyst, wherein the mass ratio of glutamic acid, intermediate 1, and p-toluenesulfonic acid catalyst is 1:1.2:0.03, react at 100°C for 8h, and then distill under reduced pressure and wash to obtain intermediate 2; (5) Add 5 parts by weight of the intermediate 2, 12 parts by weight of an aqueous solution of formaldehyde, and 22 parts by weight of phenol into a toluene solvent, fully dissolve them, and carry out a cyclization reaction at 85° C. for 13 hours. After the reaction, distill under reduced pressure, wash with deionized water, and recrystallize the crude product from dichloromethane to obtain an amino acid-based benzoxazine; (6) 13 parts by weight of polymethyl terephthalate, 6 parts by weight of carbon fiber, 16 parts by weight of phenolic resin, 7 parts by weight of quaternary ammonium salt-modified graphene oxide, 5 parts by weight of amino acid-based benzoxazine, and 1 part by weight of bentonite were added into a stirrer and stirred at 600 rpm for 2.5 hours to obtain an anti-corrosion material containing polymethyl terephthalate.

[0017] Comparative Example 1 Compared with Example 3, this comparative example is different in that no quaternary ammonium salt is added to modify the graphene oxide.

[0018] Comparative Example 2 Compared with Example 3, this comparative example is different in that no amino acid-based benzoxazine is added.

[0019] Use an oxygen index meter to test the limiting oxygen index of anti-corrosion materials; use a horizontal and vertical combustion instrument to test the combustion level of anti-corrosion materials.

[0020] Table 1: Flame retardancy tests.

[0021] project Limiting oxygen index (%) Combustion level Example 1 29 V-0 Example 2 31 V-0 Example 3 35 V-0 Comparative Example 1 21 V-1 Comparative Example 2 22 V-1 It can be seen from Table 1 that the flame retardant effect of Examples 1-3 is better than that of Comparative Examples 1-2, which indicates that the anti-corrosion material prepared by the present invention has good flame retardant effect.

[0022] Neutral salt spray test: A neutral salt spray test was conducted using an SH-60 salt spray test chamber. The samples obtained in the embodiment and the comparative example were coated on the surface of a steel plate with a size of 150 mm × 70 mm × 1 mm. The surface of the steel plate was polished with 100-mesh sandpaper in advance and washed with anhydrous ethanol to obtain the sample to be tested. The coating was first sealed with paraffin to prevent the surrounding environment from affecting the coating surface. The treated coating was subjected to a salt spray test. The test coating sample was placed in the test chamber at a certain angle. A 5% Na Cl solution was prepared and added to the salt water storage device of the salt spray chamber. The temperature was set to 35°C, and then a continuous neutral salt spray test was conducted. The test cycle was 720 hours. During the test, the changes in the surface of each group of coating samples were recorded and observed. After the neutral salt spray test was completed, the corroded macroscopic sample surface was rated according to the standard. The test results are shown in Table 2.

[0023] Table 2: Salt spray test.

[0024] project Protection Rating (RP) Example 1 9 Example 2 9 Example 3 9 Comparative Example 1 8 Comparative Example 2 8 It can be seen from Table 2 that Examples 1-3 have better salt spray resistance than Comparative Examples 1-2, indicating better anti-corrosion effect.

[0025] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An anticorrosive material containing polymethyl terephthalate, characterized in that: The invention comprises the following components by weight: 10-15 parts by weight of polyethylene terephthalate, 4-8 parts by weight of carbon fiber, 8-20 parts by weight of phenolic resin, 4-9 parts by weight of quaternary ammonium salt-modified graphene oxide, 3-7 parts by weight of amino acid-based benzoxazine, and 1-2 parts by weight of bentonite.

2. The anticorrosive material containing polymethyl terephthalate according to claim 1, characterized in that: The preparation method of the quaternary ammonium salt modified graphene oxide is: (1) Under a nitrogen atmosphere, add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to tetrahydrofuran solvent, stir and dissolve, continue to add azobisisobutyronitrile initiator and di(dimethylamino)methylvinylsilane, react at 65-85°C for 10-14h, and after the reaction is completed, distill under reduced pressure and vacuum dry for 6-8h to obtain phosphorus-containing tertiary aminosilane; (2) Add 2,2-bis(bromomethyl)-1,3-propylene glycol and phosphorus-containing tertiary aminosilane to acetone solvent, stir evenly, then continue to add 3-5 mol / L sodium hydroxide aqueous solution, react at 75-90°C for 4-6 hours. After the reaction is completed, neutralize, concentrate, filter, wash and dry to obtain intermediate 1 (3) Ultrasonic dispersion of 5-8 parts by weight of graphene oxide in 45-70 parts by weight of thionyl chloride, after uniform dispersion, reacting at 50-75° C. for 3-6 hours to obtain acylated graphene oxide; adding acylated graphene oxide and intermediate 1 into N,N-dimethylformamide solvent, stirring and mixing, continuously adding triethylamine catalyst thereto, reacting at 70-90° C. for 4-7 hours, and then distilling under reduced pressure, washing and drying to obtain quaternary ammonium salt-modified graphene oxide.

3. The anticorrosive material containing polymethyl terephthalate according to claim 2, characterized in that: The mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, azobisisobutyronitrile initiator and bis(dimethylamino)methylvinylsilane in (1) is 1:0.01-0.03:1.1-1.

4.

4. The anticorrosive material containing polymethyl terephthalate according to claim 2, characterized in that: The mass ratio of 2,2-bis(bromomethyl)-1,3-propylene glycol to phosphorus-containing tertiary aminosilane in (2) is 0.9-1.2:

1.

5. The anticorrosive material containing polymethyl terephthalate according to claim 2, characterized in that: The mass ratio of the acylated graphene oxide, the intermediate 1, and the triethylamine catalyst in (3) is 1.3-1.5:1:0.02-0.

04.

6. The anticorrosive material containing polymethyl terephthalate according to claim 1, characterized in that: The preparation method of the amino acid-based benzoxazine is as follows: S1. Add glutamic acid to N,N-dimethylformamide solvent, stir to dissolve, continue to add intermediate 1 and p-toluenesulfonic acid catalyst, react at 90-110°C for 6-10h, and then distill under reduced pressure and wash to obtain intermediate 2; S2. Add 4-6 parts by weight of intermediate 2, 10-15 parts by weight of an aqueous solution of formaldehyde and 18-24 parts by weight of phenol into toluene solvent, fully dissolve them, and carry out cyclization reaction at 70-95°C for 10-16 hours. After completion, distill under reduced pressure, wash with deionized water, and recrystallize the crude product from dichloromethane to obtain amino acid-based benzoxazine.

7. The anticorrosive material containing polymethyl terephthalate according to claim 6, characterized in that: The mass ratio of glutamic acid, intermediate 1 and p-toluenesulfonic acid catalyst in S1 is 1:1.1-1.4:0.02-0.

04.

8. A method for preparing an anticorrosive material containing polymethyl terephthalate according to any one of claims 1 to 7, characterized in that: The preparation method of the anti-corrosion material containing polymethyl terephthalate is as follows: polymethyl terephthalate, carbon fiber, phenolic resin, quaternary ammonium salt-modified graphene oxide, amino acid-based benzoxazine and bentonite are added into a stirrer, and stirred at 550-700 rpm for 2-3 hours to obtain the anti-corrosion material containing polymethyl terephthalate.

Citation Information

Patent Citations

  • Corrosion-resistant materials and their preparation methods

    CN103184001B

  • Phosphaphenanthrene silane grafted modified graphene and preparation method thereof

    CN111269461A

  • Environment-friendly flame-retardant transparent polyester material

    CN112679933A

  • Graphene oxide quaternary ammonium salt type corrosion inhibitor as well as preparation method and application thereof

    CN118271202A

  • Electronic glue containing modified butadiene rubber and preparation method thereof

    CN118652649A